(untitled) - Biringucci, Vannoccio (Cambridge, Mass., 1942)
This book introduce about Pirotechnia of Vannoccio Biringuccio a medieval metal mining and metal working treatise.
Keywords: Luyện kim,Metal-work; Trước năm 1800,Early works to 1800